Forms of Education and the Teacher's Empowerment - Małgorzata Kabat (Maria Curie-Skłodowska University, Lublin, Poland, 2024)
Introduction: Educational transformations in Poland and the world are the reason for undertaking the modernisation of the teacher's professional activities. A key issue is becoming the requirement for the teacher to acquire knowledge about the organisation of the school process that ensures the most effective realisation of goals, tasks and functions.  Solutions are sought in this area that include harmonizing the teacher's natural organisational skills with his/her knowledge dependent on his/her talents, pedagogical experience exploited in complex educational forms and situations. Research Aim: The aim of the research was combined with the recognition of the teacher's involvement in the professional activity necessary in the organisational activities emblematic of the forms of school and non-school reality discussed. A deductive method of data analysis combining with the selection of selected sources was used, focusing on descriptive and new implementation. Evidence-based Facts: The exploration carried out revealed that the considered forms of education function independently as well as interpenetrate each other, creating a common ground for the emergence of teacher empowerment, which is the impulse for the emergence of a new personal-team structure in the educational process. Summary: The theoretical and exploratory analyses made show a glimpse that the application in various forms of education of teacher empowerment and its assumptions together with the PERFORM model is an alternative way of combining educational theory and practice representing a different remedy of professional functioning.